Road Detection Using Data From Mobile Robot Camera - Peška, Jaroslav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
The paper is focused on developing a road detection algorithm that uses only data from a mobile robot’s camera. Key requirements are low latency and relatively low power requirements. Presented algorithm makes use of machine learning, where the neural network is fed not only image data, but also select additional inputs.
Keywords: road detection; image processing; neural network; machine learning; obstacle avoidance